The Influence of Emotional Intelligence, Intellectual Intelligence and Job Satisfaction on the Performance - Ameliya, Kenny Riva; Rinaldo, Jhon; Lubis, D (Adabi : Journal of Public Administration and Business, 2023)
This research is motivated by a decrease in the target quantity of work that can be realized. This study aims to: 1) partially analyze the influence of emotional intelligence on the performance of PDAM Padang City employees. 2) Analyze the influence of intellectual intelligence partially on the performance of PDAM Padang City employees. 3) Analyze the effect of partial job satisfaction on the performance of PDAM Kota Padang employees. The population of this research is all employees in the field of distribution at PDAM Kota Padang, as many as 268 people. The sampling technique in this study was a proportional random sampling technique using the Slovin formula to obtain a sample size of 166. The data analysis technique used in this study was multiple regression analysis. Based on the research results, the conclusions of this study can be described as follows: 1) Emotional intelligence has a positive and significant effect on employee performance at PDAM Kota Padang. That is, the higher the level of emotional intelligence of employees, the more 2) Intellectual intelligence has a positive and significant effect on employee performance at PDAM Kota Padang. 3) Job satisfaction positively and significantly affects employee performance at PDAM Kota Padang.